2012
DOI: 10.1080/13607863.2011.651432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of social capital and personal autonomy on the incidence of depressive symptoms in the elderly: Evidence from a longitudinal study in Mexico

Abstract: PA and SC proved to be protective factors against the onset of DS in women. For men, only PA was a protective factor. Future studies need to explore in what ways that PA and SC may reduce risk of DS as well as the role of gender differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 47 publications
2
36
0
8
Order By: Relevance
“…In line with other recent studies on OA, we found significant association between the presence of depressive symptoms and a number of variables at the individual level, in particular: female [17], [40][43], absence of an intimate partner [17], [41][43], a low educational level or illiteracy [17], [41][42], lack of empowerment in household decision-making (especially with regard to financial matters) [43][44], disability or functional limitations [40][41], presence of comorbidity [40][43], and chronic exposure to psychosocial stress [42]. The latter could be an important factor in the strong connection we found between depressive symptoms and self-reported incidents of physical violence or accidents in the previous 12 months.…”
Section: Discussionsupporting
confidence: 93%
“…In line with other recent studies on OA, we found significant association between the presence of depressive symptoms and a number of variables at the individual level, in particular: female [17], [40][43], absence of an intimate partner [17], [41][43], a low educational level or illiteracy [17], [41][42], lack of empowerment in household decision-making (especially with regard to financial matters) [43][44], disability or functional limitations [40][41], presence of comorbidity [40][43], and chronic exposure to psychosocial stress [42]. The latter could be an important factor in the strong connection we found between depressive symptoms and self-reported incidents of physical violence or accidents in the previous 12 months.…”
Section: Discussionsupporting
confidence: 93%
“…El apoyo social ha sido mostrado, en diferentes publicaciones, como un factor que puede aliviar los síntomas depresivos, tanto en su vertiente afectiva (Webber et al 2011), como en su vertiente confidencial (Zhang y Li 2011). En una investigación reciente realizada en México (Bojorquez-Chapela et al 2012) se matiza que es el capital social, más que el apoyo social (un concepto más restringido que el de capital social), el que resulta determinante para los síntomas depresivos de las personas mayores.…”
Section: Discussionunclassified
“…Para observar el posible efecto modificador del sexo (30), se incluyeron algunos términos de interacción con variables del nivel individual (etnia, vivir con pareja, tener trabajo remunerado, fumar y beber alcohol), así como con variables relativas a la localidad (localidades urbanas y marginación), y la variable de interés relacionada con el estado (índice de biodiversidad). El nivel socioeconómico se estableció individualmente según el ingreso mensual y, a nivel de localidad, mediante el índice de marginación (31).…”
Section: Variablesunclassified